Gender-related differences in self-rating of health and functional status of elderly people with ischaemic heart disease. Comparative study in 12-year period - Tobiasz-Adamczyk, B; Brzyski, P (Central European journal of public health, 2002)
PURPOSE OF THE STUDY: The study aim is to present changes in the self-rating of health and functional status in performing activities of daily living, reported by the elderly persons with ischaemic heart disease (IHD), at the time interval of 12 years. Gender-related differences as well as socio-medical characteristics have been involved in the analysis changes. DESIGN AND METHODS: The study was carried out in 607 elderly respondents who participated in two surveys at the time interval of 12 years. The analysis of the functional ability in performing daily activities in both surveys was based on the ADL and IADL scales, self-rated health was based on the scale ranging from very poor to excellent health. RESULTS: It has been observed in the baseline survey that the respondents with IHD reported lower mobility, functional activity and scored their health lower than other respondents. Though females with IHD scored higher their functional ability than males with the same disease, decrease of their functional ability at the time interval between both surveys was three-fold higher compared to males with the same disease. The results of the second study demonstrated age-related level of self-coping with the activities of daily living (ADL scale) in females with IHD, while none of the factors from the baseline survey had influence on their functional independence (irrespective of IHD). Functional status in the second study of males with IHD has been influenced by age and presented in baseline study willingness to life, while in males who have not reported IHD, any factor coming from the 1st survey have not determined the level of independence in activities of ADL in survey II. Functional ability in males with IHD was affected in the IInd study, besides age, by the attitude denying weariness of life demonstrated in the baseline survey. None of the factors from the baseline survey determined self-coping with daily activities by the males without IHD as it was observed in the IInd study.
Keywords: Poland; Aged; Chi-Square Distribution; neparametrická statistika; Statistics, Nonparametric; senioři; Activities of Daily Living; Self Disclosure; činnosti denního života; zdravotní stav; lidé; Sex Factors; průzkumy a dotazníky; Female; Health Status; Polsko; Surveys and Questionnaires; Male; ženské pohlaví; sexuální faktory; Humans; mužské pohlaví; sebeodhalení; ischemická choroba srdeční; Myocardial Ischemia; regresní analýza; rozdělení chí kvadrát; Regression Analysis